(untitled) (Experimental biology, 2023)
A comparative analysis of the genetic diversity and variability of horse populations bred in Kyzylorda and Karaganda regions was made on the basis of 25 microsatellite markers. All loci used in the study were polymorphic. The genetic polymorphism of the studied populations was compared with horse populations bred in neighboring countries. The results of the comparative analysis showed that the individuals in the study sample had a high level of genetic diversity.